Impact of Fetal Growth and Preterm Birth on the Retinal Microvasculature in Mid‐Adulthood. (May 2015) - Hussain, Sultana Monira; Kähönen, Mika; Raitakari, Olli T.; Skilton, Michael R.; Witt, Nicholas; Chaturvedi, Nish; Hutri‐Kähönen, Nina; Lehtimäki, Terho; Vaahtoranta‐Lehtonen, Hanna; Juonala, Markus; Wijetunge, Sumangali; Hughes, Alun D.; et al.
Abstract: Objective: We hypothesized that preterm birth and being born SGA would be associated with changes in retinal microvascular architecture and that these changes would be more marked among those born preterm. We further hypothesized that these microvascular changes would correlate with early markers of CVD in mid‐adulthood. Methods: The Cardiovascular Risk in Young Finns Study included randomly selected children from 5 Finnish University cities. Retinal microvascular architecture of participants born preterm, born at term and SGA and a control group born at term and AGA were compared (aged 34–49 years). Results: In participants born preterm, arteriolar tortuosity (×10 2 ) was higher—means (standard error), 0.06 (0.01) versus 0.04 (0.01), p =  0.001, arteriolar length (pixels) were greater—644.9 (35.9) versus 591.7 (33.5), p =  0.007 and arteriolar diameters (pixels) were narrower—19.9 (0.4) versus 20.3 (0.3), p =  0.034 compared to participants born AGA, after adjustment. In participants born SGA, only arteriolar tortuosity was higher—0.05 (0.01) versus 0.04 (0.01), p =  0.074 compared to participants born AGA. Conclusion: This study demonstrated that being born SGA and in particular preterm birth are associated with changes in retinal microvascular architecture. The prenatal and immediate postnatal environment may contribute to the mechanisms.